2006
DOI: 10.1007/s00125-006-0495-x
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 diabetes and cardiovascular risk in the UK south Asian community

Abstract: Unfortunately the authors of reference 53 were incorrect. The correct reference is:53. Mohan V, Deepa R, Haranath SP et al. (1998) Lipoprotein(a) is an independent risk factor for coronary artery disease in NIDDM patients in South India. Diabetes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
69
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(71 citation statements)
references
References 0 publications
1
69
1
Order By: Relevance
“…People in South Asian countries have earlier incidence and greater premature mortality from cardiovascular disease (CVD) than people in Western countries, a disparity that persists for South Asian immigrants in developed countries [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. A case-control comparison of age of first acute myocardial infarction between five South Asian countries and 47 other countries concluded that the observed disparities could be attributed to higher levels of standard risk factors at earlier ages in South Asians compared to citizens of other countries [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…People in South Asian countries have earlier incidence and greater premature mortality from cardiovascular disease (CVD) than people in Western countries, a disparity that persists for South Asian immigrants in developed countries [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. A case-control comparison of age of first acute myocardial infarction between five South Asian countries and 47 other countries concluded that the observed disparities could be attributed to higher levels of standard risk factors at earlier ages in South Asians compared to citizens of other countries [5].…”
Section: Introductionmentioning
confidence: 99%
“…In California, South Asian men ages 25-44 years have three times the relative risk of death from CVD in comparison to the age-matched general population [4]. Epidemiologic studies have documented that South Asian immigrants have higher prevalence of medical CVD risk factors than the general population, such as diabetes, dyslipidemia, and metabolic syndrome, possibly due to a genetic predisposition to insulin resistance and central adiposity [6,9,11,[22][23][24][25][26][27][28][29]. They also have high rates of behavioral CVD risk factors, including physical inactivity and diets low in fruits and vegetables [9, 23-25, 28, 30, 31].…”
Section: Introductionmentioning
confidence: 99%
“…Diabetic retinopathy (DR) is one of the most common microvascular complications. Common risk factors for the development of DR include duration of diabetes, poor glycemic control, elevated blood pressure, and dyslipide mia, of which the latter three are potentially amenable to therapeutic intervention (Stratton et al 2001;Barnett et al 2006). Whether SCH is related to DR in type 2 diabetic patients remains controversial.…”
mentioning
confidence: 99%
“…One of the characteristics that most strongly influences occurrence in the UK population is South Asian origin (27,28) . It has been estimated that 6 .…”
Section: Service Provisionmentioning
confidence: 99%